Validating and identifying KPIs in ATP/WTA hard court tennis match play (2019-2023) using the PWOL method - Venn-Moncur, M. J.; Parmar, N.; White, C. J.; Callingham, T.; Nicholls, S. B. (International Journal of Sports Science & Coaching, 2024)
The study provided further validity for the use of the PWOL (percentage of matches which the winner outscored the loser) method within elite hard-court tennis. Over half of the ATP/WTA competitive calendar (January-March and August-November) is played on hard courts so is an important progression. Data from 810 men's and 586 women's hard-court matches across Grand Slams and ATP/WTA World Tours (i.e. Masters, 500s and 250s) between 2019 and 2023 was used for analysis. PWOL was validated alongside two traditionally used statistical methods (paired t-test, point-biserial correlation). Very high agreement between all approaches was shown using Spearman's correlation analysis for both men and women (>0.97). The study further identified the indicators most related to winning performance, identifying baseline points won, first serve points won, points won of 0-4 rally length and Winners:UE Ratio to be most strongly associated with success, whilst forced errors were most associated with losing. Ball three indicators lacked association with match outcome, suggesting any major focus training `one-two punches` on serve should be approached with caution. PWOL has proven to be a valid method for assessing success in elite hard-court tennis (offering potential for wider sports application) to ultimately aid coach decision-making.